(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
The purpose of this paper was to determine the relationship between diversification strategies and business performance of food and beverages firms. The population of the study consisted of 177 employees drawn from 10 of the firms. Two research questions and two hypotheses were asked and formulated respectively. The sampling method adopted was the non-probability sampling method for convenience purposes. Thus, the census of the population was studied. Data for the study was sourced through structured questionnaire and personal interview methods and analysed using the Spearman Rank Order Correlation Coefficient in line with SPSS version. Findings from the analysis revealed a positive and significant relationship between diversification strategies and business performance of food and beverages firms. The study therefore recommended that considering the changing nature of the environment and competitiveness in the industry, food and beverages firms should pursue diversification strategies to achieve growth and profitability which are some of the measures of business performance.